Biochemical changes of kemiri sunan [Reutealis trisperma (Blanco) Airy Shaw] kernels at eight levels of fruit storage duration. Issue 1 (January 2022) - Virgian, S; Aunillah, A; Listyati, D; Herman, M; Pranowo, D; Wardiana, E
Abstract: Kemiri Sunan [ Reutealis trisperma (Blanco) Airy Shaw] fruit harvest is carried out according to physiological maturity, indicated by the fruit's natural fall from the tree. The fruit collection period can take up to several days according to the processing mill's minimum capacity. Constraints like this result in fruit collected at an earlier harvest cycle that will undergo a storage process for up to several days. The study was conducted at Pakuwon Experimental Station and Integrated Laboratory, Balittri, Sukabumi, West Java. This study investigates the biochemical changes of Kemiri sunan kernels at eight levels of fruit storage duration. The design used was completely randomized with eight treatments and three replications. The eight treatments were the fruit storage duration: 0 days (without storage) and storage for 2, 4, 6, 8, 10, 12, and 14 days. The variables observed were the kernel's moisture, ash, oil, protein, peroxide, and free fatty acids (FFA) content. The results showed that fruit storage decreased moisture and oil content but increased FFA content. Storage of fruit up to a maximum of 8 days does not change the kernels' biochemistry, indicating that the fruit is still suitable for further processing.